Giant serous microcystic pancreas adenoma - Dikmen, Kursat (PAGEPress Publications, 2012)
Serous cystadenomas are rare tumors comprising 1–2% of exocrine pancreas tumors. They are mostly known as benign conditions but malign transformation as serous cystadenocarcinoma is also reported. It is usually seen in females. Non-specific symptoms, such as abdominal pain or symptoms due to mass affect, are usually seen. A 64-year old female patient was investigated for abdominal pain. Physical and laboratory findings were normal. Abdomen ultrasonography confirmed an 11×9.5 cm solid cystic lesion and abdomen computed tomography scan confirmed a 12×11 cm lobulated cystic solid lesion which had central cystic necrotic areas extending from liver hilus inferiorly. Fine needle biopsy confirmed benign cytology and trucut biopsy of the pancreatic mass reported chronic inflamation. Nevertheless, this mass could have malignant contents and transformation potential. A laparatomy was decided due to patient's symptoms and mass effect. Due to vascular invasion of the tumor, Whipple procedure was performed. The pathology report confirmed serous microcystic adenoma. These rare tumors are usually benign but pre-operative malignity criterias are not identified. There are few differential diagnostic tools for excluding malignity. We suggest surgical resection as best treatment approach for selected cases.